The effect of cold pack on pain reduction during sub cutaneous injection of - massoompour, Anahita; Zaeeri, Farid; Dabirian, Akram (Advances in Nursing & Midwifery, 2012)
Abstract: Background and aim : Cancer is the most common cause of morbidity in children over 1 year in the west and is also prominent in the developing countries in the world. The disease and its treatment consisting of chemotherapy, radiation therapy and surgery can cause pain. The nurses are responsible to reduce the mental and physical effects of the pain. Localized cooling may reduce the pain of sub cutaneous injections considerably. The aim of this study was to determine the effect of cold pack on pain induced by GCSF injection in cancerous children attended to selected hospital in Tehran(Iran) in 2010. Method and materials : A cross-over clinical trial was conducted to assess the usefulness of ice pack for relieving pain induced by GCSF injections . A convenience sample of 35 children with cancer receiving GCSF injections were included in the study. These children were randomly assigned to either application of ice pack for a duration of 3 minutes prior to s.c injection of GCSF or routin care. crossing over for the next day of injection .The site of injection was The upper most of the of arm and the amount of prescribed GCSF was atmost 0/5-1 cc for each injection . All injections was carried out by the same nurse. The data collection tools were a demographic questionnaire (age, sex, and birth order,and etc) and behavioural criteria of cheopes for pain assessment .The injection was done by one nurse and pain evaluation was evaluated by another nurse who had no idea about the manner of injection each time.Data were data analysed by SPSS 16 . Result : The analysis of repeated measures showed The mean age of children was 8.5 years with Standard deviation of 2.17.Repeated measures analysis showed a significant difference of pain score between ice pack and control group . The analysis also showed that the only contributing variable was the age of childe (P=0.023). The older children, reported more pain severity after and during injection. Conclusions: The result of this study showed the useful effect of ice pack in reduction pain during subcutaneous injections in children. Using this method for reducing pain will result in better cooperation of children in following-up their treatment appoinments .It is recommended that more research should be done in this area. Key words: Chemotherapy – Ice pack- pain- GCSFinjection. S.C injection